The Upside Potential of Hiring Risky Workers: Evidence from the Baseball Industry - Bollinger, Christopher R.; Hotchkiss, Julie L. (Journal of Labor Economics, 2003)
Making use of performance data for baseball players, this article provides empirical evidence in support of Lazear’s (1998) theoretical predictions that (1) risky workers will earn a premium for their upside potential, (2) this risk premium will be higher the longer a worker’s work life, and (3) firms must enjoy some comparative advantage in the labor market to be willing to pay a premium to risky workers. The validity of Lazear’s predictions carries implications for wage differentials between young and old workers and between men and women.